Implementation of Fuzzy-PID Controller for 2-DOF Helicopter - Huynh, Thanh-Do; Bach, Ngoc-Thanh; Le, Quang-Dao; Le, Duong-Dong; Bui, Viet-Hoang; Vo, Hoai-An; Nguyen, Viet-Nhat-Long; Pham, Phi-Hung; Nguyen, Huu-Dat; Nguyen, Van-Dong-Hai (Peneliti Teknologi Teknik Indonesia, 2024)
This article presents the model and control of a 2-DOF helicopter, a multi-input multi-output (MIMO) system that is set up in the laboratory. The conventional mathematical model, employing the Euler-Lagrange method, is utilized in this study to conduct the system modeling process. The transfer functions derived from this model are then incorporated into diverse control methodologies to optimize PID gain coefficients. The PID controllers are employed to control this system. In addition, we use a Fuzzy controller to adjust the Kp, Ki, and Kd coefficients of this PID. As a result, we obtain a fuzzy PID controller with superior control quality than a PID controller. Under Fuzzy-PID, the system operates more stably, overcoming some weaknesses of the PID linear controller. The state space model is built by considering specific design assumptions and simplifications. Results are obtained through simulation and testing on the model.